The constraints of cancellation of the final exam of physical education and sports on the work teachers in the science of EPS. - Touati , Hayet; Benkhaled, hadj; Atallah, Ahmed (sports creativity, 2025)
The objective of this research is to know the extent to which the cancellation of sports education final examination influences on the work of teachers responsible for the final classes and pupils of such classes. Thus, we adopted a main question: will the cancellation of the final examination of physical education and sports influence the work of the teacher and the learner in physical and athletic education sessions? We assumed that the cancellation of the final exam would have some influence on the work of the teacher and the learner in the physical education sessions. To test this hypothesis, we use a descriptive method using a questionnaire sent to 155 teachers in charge of final classes (pupils in 3rd A.S ,the 4th year AM). After retrieving the answered questionnaires, we treated the responses using a variety of statistical. The analysis of the data from the questionnaires confirmed that the cancellation of the final examination of physical education and sports did indeed influence the work of the teachers, who invented new evaluation strategies, to impose more disciplines in working sessions. As for the students, they were obliged to prove more discipline and attendance in physical education and sports sessions. In conclusion, we can present some proposals, including the need to unify the assessment scale at the national level for all individual and collective activities and the need for the teacher to have a strong influential personality to master the classes and to give pupils good